A rare presentation of genital self-mutilation in a patient of schizophrenia - Tabrez, Md. Omar; Aziz, Md. Tabrez (International Surgery Journal, 2017)
Genital self-mutilation (GSM) is an uncommon self-inflicted injury. GSM is not a single clinical entity, and it can occur in any psychiatric state or condition. The instruments that are used for self-mutilation can vary, and treatment of these injuries requires a detailed clinical evaluation and multi-disciplinary approach. We report here a case report of a 28-year-old psychotic man who came to our emergency with complaint of self-hammered nails in his both scrotum with fear of not able to reproduce child after marriage. He underwent surgical removal of nail under local anaesthesia and was promptly reviewed by the psychiatrists who managed appropriately. To our knowledge this is the first case reported in literature and the rarest type of injury presented as a bilateral scrotal self-mutilation as should be managed wisely.